2017
DOI: 10.1101/156869
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bat Detective - Deep Learning Tools for Bat Acoustic Signal Detection

Abstract: Summary1. Passive acoustic sensing has emerged as a powerful tool for quantifying anthropogenic impacts on biodiversity, especially for echolocating bat species.To better assess bat population trends there is a critical need for accurate, reliable, and open source tools that allow the detection and classification of bat calls in large collections of audio recordings. The majority of existing tools are commercial or have focused on the species classification task, neglecting the important problem of first local… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(57 citation statements)
references
References 56 publications
0
57
0
Order By: Relevance
“…An early use of this in bioacoustics can be seen in the work of Halkias et al (2013) 191 that demonstrated the ability of deep Boltzmann machines to distinguish mysticete species. Deep CNNs have been used for bat species identification 204 and have become one of the dominant types of recognizers for bird species identification since the successful introduction of CNNs in the LifeCLEF bird identification task. 205 Unsupervised ML has not been used as extensively in bioacoustics but is nonetheless present.…”
Section: Bioacousticsmentioning
confidence: 99%
“…An early use of this in bioacoustics can be seen in the work of Halkias et al (2013) 191 that demonstrated the ability of deep Boltzmann machines to distinguish mysticete species. Deep CNNs have been used for bat species identification 204 and have become one of the dominant types of recognizers for bird species identification since the successful introduction of CNNs in the LifeCLEF bird identification task. 205 Unsupervised ML has not been used as extensively in bioacoustics but is nonetheless present.…”
Section: Bioacousticsmentioning
confidence: 99%
“…Given a short audio-clip we want to classify it as containing a signal produced by the species of interest (in this case an elephant rumble) or not. This setting has been considered by many previous authors (Mac Aodha et al 2018;Nichols 2016;Bittle and Duncan 2013), and is a crucial stepping stone toward using PAM for population surveying and monitoring. A similar setting we consider is one of segmentation where we want to classify each discrete time step as belonging to an elephant call or not.…”
Section: Classification and Segmentationmentioning
confidence: 99%
“…Popular strategies include SVMs based upon MFCC (Dufour et al 2014), segmentation via deep learning (Koops, Van Balen, and Wiering 2015) and dictionary learning (Salamon et al 2017). Beyond birds, insects (Ganchev and Potamitis 2007), bats (Mac Aodha et al 2018) and monkeys (Turesson et al 2016) have all been considered. Elephants have been studied from a similar perspective to ours by Pleiss, Wrege, and Gomes.…”
Section: Related Work Bioacousticsmentioning
confidence: 99%
“…Convolutional neural networks (CNNs) have been used to predict the presence of a search-phase bat echolocation call in spectrograms. This binary classification problem was used to detect the presence of bats [2]. To our knowledge, the use of deep learning techniques to separate animal calls that overlap in both time and frequency space has yet to be reported.…”
Section: Introductionmentioning
confidence: 99%
“…The primary objective of this study is to develop a technique for separating two target signals (echolocation and socialization calls) from mixtures of acoustic sounds. Although deep leaning has been employed in the acoustic classification of multiple species, including nonhuman primates [28], birds [4], whales [5], and bats [2, 3], the goal of the present study is distinct from these previous cases in which deep neural networks were primarily used as classifiers.…”
Section: Introductionmentioning
confidence: 99%